Exploring Canadian perceptions and experiences of stigma during the COVID-19 pandemic - Fahim, Christine; Cooper, Jeanette; Theivendrampillai, Suvabna; Pham, Ba'; Straus, Sharon E. (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic has led to stigmatization of individuals based on race/ethnicity, age, gender, and occupation, among other factors. We canvassed Canadian residents to explore perceptions of and experiences with stigma during the COVID-19 pandemic. Methods: We conducted an online survey between June 10-December 31 2020. The survey was rooted in the Health Stigma and Discrimination Framework and included multiple choice, Likert and open-ended questions related to perceived and experienced stigma. Residents of Ontario, Canada were eligible to participate and we aimed to recruit a sample that was diverse by race/ethnicity and age. Results: A total of 1823 individuals participated in the survey (54% women, 39% men; 54% 18-40 years old, 28% 41-60 years old, 12% 61+ years old; 33% White, 26% East/SouthEast Asian, 14% Black, 12% South Asian). Fifty-one percent of participants agreed/strongly agreed that racist views had increased towards certain racial/ethnic groups in Canada during the pandemic. Participants perceived that people in Canada were stigmatized during the pandemic because of race/ethnicity (37%), political beliefs (26%), older age (24%), being a healthcare worker (23%), younger age (22%), being an essential worker (21%), and gender (11%). Thirty-nine percent of respondents feared experiencing and 37% experienced stigmatization during the pandemic. Men, individuals aged 18-40, and non-White participants were more likely to fear or experience stigma. With respect to health behaviours, 74%, 68%, and 59% of respondents were comfortable masking in public, seeking medical care if they became ill, and getting tested for COVID-19, respectively. Men were less likely to indicate comfort with mask wearing or seeking medical care. Participants aged 18-40 and Black participants were less likely to indicate comfort with all three behaviours compared to those over age 41 and White participants, respectively. South Asian participants were less likely to be comfortable seeking medical care compared to White Participants. Discussion: Participants feared or experienced stigmatization during the COVID-19 pandemic because of various demographic characteristics. It is critical that the factors driving stigma during health emergencies in Canada be better understood in order to develop effective public health messaging and interventions.